The Impact of Congklak Games on The Cognitive Development of Children Aged 5-6 Years - Hidayah, Nur; Fauziyah, Nur (Universitas Muhammadiyah Surakarta, 2023)
Traditional games are one of the concepts of learning while playing. Congklak is one of the traditional games that can stimulate the cognitive development of Early Childhood. This study aims to determine the impact of playing congklak on the cognitive abilities of children aged 5-6 years at Aisyiyah 02 Beruk Kindergarten, Jatiyoso District. By using a descriptive approach and qualitative research. The subjects in this study were teachers and Kindergarten B children, while the objects were 20 children in Kindergarten B class. Data collection techniques in the form of observation, interviews and documentation. Data analysis uses the Miles and Huberman models including data reduction, data presentation, and verification or drawing conclusions. The results of the study stated that the traditional game of congklak can improve cognitive development of early childhood with significant results, namely the results of cycle I showed that out of 20 children, 5 children (25%) had achieved learning mastery. Cycle II showed that out of 20 children, 8 children (40%) had achieved learning mastery. And cycle III shows that out of 20 children, 13 children (65%) have achieved learning mastery.